The influence of characteristics of a child with autism spectrum disorder on the psychological well-being of parents - PASICHNIAK, Ruslana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. The ability of parents to effectively promote the development and successful adaptation of children with autism spectrum disorders depends on their own emotional states and psychological well-being. Parents' subjective evaluation of their child's difficulties stemming from autism symptoms significantly affects their sense of self and overall life satisfaction. The aim of the study was to identify the influence of a child's characteristics on the main indicators of psychological well-being in parents.Methods. Empirical data were obtained through a questionnaire method (author's questionnaire) and the "Psychological Well-being Scale" by Carol D. Ryff, and their processing was carried out using the nonparametric statistical criterion of Mann-Whitney and the Kendall's Tau-b method.Results. The findings revealed a predominant low level of psychological well-being, particularly concerning parents' perceptions of personal growth (50% of the surveyed respondents reported a low level of this indicator). Satisfaction in the areas of environmental management, personal growth, positive relationships with others, and self-acceptance tends to decline with an increase in the number of difficulties caused by the diagnosis of autism spectrum disorders. No significant differences in psychological well-being indicators were found in relation to children's speech and sensory issues.Conclusions. The most sensitive aspects of the psychological well-being of parents raising children with autism spectrum disorders were identified as: "Environmental management", "Personal growth", "Positive relationships with others", "Self-acceptance" (including the number of types of difficulties, behavioral issues, sleep disorders), and "Life goals". Behavioral problems, their frequency, and sleep disorders were the most significant factors influencing differences in the levels of psychological satisfaction of caregivers.
Keywords: autism spectrum disorder; psychological well-being; personal growth; positive relationships with others; environmental management; self-acceptance